Operative Dentistry A Practical Guide to Recent Innovations - Devlin, Hugh. (Springer Berlin Heidelberg : Imprint: Springer, 2006)
This book describes the most recent developments in the field of operative dentistry. It is aimed at senior students and general dental practitioners and describes techniques and methods in a step-by-step manner that is directly applicable to everyday practice. It is a short, readable textbook with plenty of high-quality color clinical figures used throughout. This book describes contemporary developments in operative dentistry. It covers recent developments in caries detection techniques and treatment, as well as the use of the latest composite and porcelain restorative materials, bleaching and crown provision techniques. There is a chapter on non-carious tooth tissue loss, which is an increasingly common problem through the widespread consumption of carbonated beverages. This book provides enough practical detail for the dentist to feel confident in expanding old skills and trying new ones. The plethora of new dental materials and techniques can prove daunting, but guidance is given as to which material or technique will prove most useful in particular circumstances.